2021
DOI: 10.1016/j.jare.2020.12.010
|View full text |Cite
|
Sign up to set email alerts
|

A value-added application of eugenol as acaricidal agent: The mechanism of action and the safety evaluation

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…As reported in the study of Shang et al, 24 eugenol inhibited a respiratory chain activity resulting in the death of mites. Insect cells were particularly sensitive to eugenol.…”
Section: Analysis Of Bio-oils and Fractions Figure 2 Presents The Rec...mentioning
confidence: 54%
“…As reported in the study of Shang et al, 24 eugenol inhibited a respiratory chain activity resulting in the death of mites. Insect cells were particularly sensitive to eugenol.…”
Section: Analysis Of Bio-oils and Fractions Figure 2 Presents The Rec...mentioning
confidence: 54%
“…Based on Table 2, this compound has been reported in baijiu and sugar-beet vinasses. The eugenol (4-allyl-2-methoxyphenol) found in tequila vinasse (Table 2); it is an acaricidal agent, having fungicidal and bactericidal activities (Abd El-Baky and Hashem 2016; Shang et al 2020). Oleuropein shows bactericidal and fungicidal activities, mainly contained in olives (Bisignano et al 1999), and, as shown in Table 2, was also in the wastewater.…”
Section: Active Compoundsmentioning
confidence: 99%
“…The modes of action of these natural bioactive compounds are under intense investigation, although some of them have been relatively well described. Figure 1 depicts some of the bioactivities exhibited by each compound described above and the modes of action by which they are exerted [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%